PENGARUH RASIO LIKUIDITAS, AKTIVITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING - Taslim, Fadli Ali (Jurnal Manajemen Sinergi, 2015)
This research aims to understand the effect of liquidity, activity, and profitability toward the company’s value throught dividend policy as intervening variable. This research’s population is manufacturing companies listed in Indonesia Stock Exchange (BEI). Samples are chosen by the method of purposive sampling which resulted in 21 samples with 5 years time span that is from 2010 to 2014. Research results shows that liquidity (CR) has positive effect towards company’s value which is proxied with Tobins Q, but also has a significant and negative effect towards company’s value through dividend policy (DPR). Activity (TATO) has negative effect towards company’s value which is proxied with Tobins-Q, but it has positive effect towards company’s value through dividend policy (DPR). Profitability (ROE) has negative effect towards company’s value which is proxied with Tobins-Q, but has positive effect towards company’s value through dividend policy (DPR).